2015
DOI: 10.1371/journal.pone.0141959
|View full text |Cite
|
Sign up to set email alerts
|

Potential Response to Selection of HSP70 as a Component of Innate Immunity in the Abalone Haliotis rufescens

Abstract: Assessing components of the immune system may reflect disease resistance. In some invertebrates, heat shock proteins (HSPs) are immune effectors and have been described as potent activators of the innate immune response. Several diseases have become a threat to abalone farming worldwide; therefore, increasing disease resistance is considered to be a long-term goal for breeding programs. A trait will respond to selection only if it is determined partially by additive genetic variation. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previously in Pacific abalone, the gene expression of HSP70 and HSP40 was reported to vary among thermal-sensitive and thermal-tolerant abalones, and the thermal-tolerant line showed higher expression levels than the thermal-sensitive lines [13]. In Haliotis diversicolor, HSP70 was highly expressed in hemocytes under both thermal and pathogen stress due to activation of the immune response [32,33]. Similarly, HSP90 was more sensitive to acute thermal stress then to chronic thermal stress, which was observed in the gill of Haliotis discus [16,17], while HSP70 was observed to be sensitive to acute and chronic thermal stress in Haliotis rufescens [33,34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously in Pacific abalone, the gene expression of HSP70 and HSP40 was reported to vary among thermal-sensitive and thermal-tolerant abalones, and the thermal-tolerant line showed higher expression levels than the thermal-sensitive lines [13]. In Haliotis diversicolor, HSP70 was highly expressed in hemocytes under both thermal and pathogen stress due to activation of the immune response [32,33]. Similarly, HSP90 was more sensitive to acute thermal stress then to chronic thermal stress, which was observed in the gill of Haliotis discus [16,17], while HSP70 was observed to be sensitive to acute and chronic thermal stress in Haliotis rufescens [33,34].…”
Section: Discussionmentioning
confidence: 98%
“…In Haliotis diversicolor, HSP70 was highly expressed in hemocytes under both thermal and pathogen stress due to activation of the immune response [32,33]. Similarly, HSP90 was more sensitive to acute thermal stress then to chronic thermal stress, which was observed in the gill of Haliotis discus [16,17], while HSP70 was observed to be sensitive to acute and chronic thermal stress in Haliotis rufescens [33,34]. Among the sHSPs, HSP20 and HSP26 were significantly expressed in muscle and mantle tissue of H. discus under thermal stress [22,35].…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 has been the focus of many studies involving summer mortality and thermal stress in abalone for several years (Brokordt et al 2015; Cheng et al 2007; Farcy et al 2007; Li et al 2012). Interestingly, the HSP70 identified in this study only demonstrated a preadaptive signature in the resilient Aquaculture abalone.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins were first reported by Tissieres et al (1974) who by exposing larvae of Drosophila melanogaster to extreme temperature, observed different proteins in the salivary glands that were not present before the heat treatment. The Hsp's can be synthesized by most of the studied species, such as mammals (Basiricò et al, 2011;Li et al, 2011), insects (Zizzari & Ellers, 2011;Calabria et al, 2012), fish (Hofmann et al, 2000;Narum & Campbell, 2010;Dalvi et al, 2012;Liu et al, 2017), mollusks (Jackson et al, 2011;Zerebecki & Sorte, 2011;Lim et al, 2012;Thompson et al, 2012;Brokordt et al, 2015) echinoderms (Dong et al, 2010) and crustaceans (Ravaux et al, 2007). In all these species groups, the heat-shock response is highly conserved, as is the sequence of the genes that control the mechanism (Kawabe & Yokoyama, 2011;Park et al, 2012;Wojstasik & Wisnik, 2012).…”
Section: Heat-shock Proteins: Features and General Aspectsmentioning
confidence: 99%
“…There are two ways in which the Hsp's can be expressed: 1) constitutively, or 2) induced (Clark et al, 2008;Witt, 2010;Jackson et al, 2011). Hsp's are produced in response to acute cellular stress (Piano et al, 2002;Farcy et al, 2009;Li et al, 2011) produced by external stressors such as drastic temperature changes, amino acid analogues, heavy metals, free radicals, environmental contaminants, immune stimulants agents, inhibitors of metabolic energy and various diseases, among others (Hooper et al, 2012;Wei et al, 2012;Malyshev, 2013;Brokordt et al, 2015;Ravaschiere et al, 2017). Wang et al (2006) observed an increased expression of Hsp70 and Hsp90 in Fenneropenaeus chinensis infected with White Spot Virus (WSSV), compared to healthy individuals, while Wei et al (2012) detected an increased expression of Hsp70 in Miichtys miiuy infected with bacteria of the genus Vibrio.…”
Section: Heat-shock Proteins: Features and General Aspectsmentioning
confidence: 99%